2004
DOI: 10.1148/radiol.2312030421
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Femoropopliteal Stenoses: Endovascular Gamma Irradiation Following Angioplasty—Angiographic and Clinical Follow-up in a Prospective Randomized Controlled Trial

Abstract: The degree of stenosis was significantly reduced 6, 12, and 24 months after angioplasty of de novo femoropopliteal stenoses in the patients who underwent endovascular irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
(35 reference statements)
1
33
1
Order By: Relevance
“…Only rarely did controlled randomized trials indicate advantages of new methods over standard treatment. [15][16][17] In the present study, the efficacy of a novel drug-coated balloon catheter for the prevention of restenosis after treatment of atherosclerotic femoropopliteal lesions was investigated. The study design included a control group treated with conventional balloon PTA, which is considered the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only rarely did controlled randomized trials indicate advantages of new methods over standard treatment. [15][16][17] In the present study, the efficacy of a novel drug-coated balloon catheter for the prevention of restenosis after treatment of atherosclerotic femoropopliteal lesions was investigated. The study design included a control group treated with conventional balloon PTA, which is considered the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there are several authors pointing out the beneficial effect of endovascular brachytherapy on restenosis reduction in the SFA. Krueger et al [29] reported a significant reduction of restenosis following PTA of de novo lesions in the femoropopliteal area in the brachytherapy group compared to the control group. Gallino et al [15] also stressed the beneficial effect of endovascular brachytherapy in fighting restenosis (17% restenosis rates in the brachytherapy group vs. 35% in the patients without brachytherapy; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Few controlled trials have been performed with brachytherapy in peripheral arterial obstructive disease. 9,[11][12][13][14] Although most of these studies reported a reduction of restenosis, a multicenter trial 14 did not demonstrate significant benefit, whereas another found no difference in restenosis with the intention-to-treat analysis approach. 13 The limitations of endovascular brachytherapy include the fact that it is sometimes technically impossible to deliver the radiation, 13 that the required vascular manipulations are cumbersome, and that they may also be associated with thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%